2015
DOI: 10.5114/pdia.2014.40983
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with leg ulcers or skin lesions – a pilot study

Abstract: IntroductionAttempts to determine the quality of life are advisable in patients with ulcers as the group affected with this problem is relatively large. According to one Polish randomized trial, approximately 0.3–2% of the adult population suffers from active or healed venous ulcers.AimTo compare the quality of life of patients with leg ulcers of venous and arterial etiology and those with lower limb skin lesions due to chronic venous insufficiency.Material and methodsThis study included 90 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
1
20
0
4
Order By: Relevance
“…Many previous studies, including research with numeric pain score which was performed in our center [ 12 , 32 ], confirmed that pain is the main determinant of poor quality of life in patients with leg ulcerations [ 2 , 6 , 8 11 , 13 , 14 , 16 , 37 ]. Additionally, a few authors point to a significant relationship between the intensity of pain and other clinical characteristics of ulceration: its area and duration of the vascular disease [ 8 , 9 , 31 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Many previous studies, including research with numeric pain score which was performed in our center [ 12 , 32 ], confirmed that pain is the main determinant of poor quality of life in patients with leg ulcerations [ 2 , 6 , 8 11 , 13 , 14 , 16 , 37 ]. Additionally, a few authors point to a significant relationship between the intensity of pain and other clinical characteristics of ulceration: its area and duration of the vascular disease [ 8 , 9 , 31 ].…”
Section: Discussionmentioning
confidence: 71%
“…Similar levels of the life quality (87.03 pts) were previously reported by Szewczyk et al . [ 12 ], who used to the same Sxindex-29 instrument in venous ulceration patients. Consequently, the quality of life in ulceration patients seems to be greater than that in individuals with psoriasis (92.65 pts) [ 25 , 35 , 36 ], but poorer than in the case of trophic disorders of the lower limb skin without associated discontinuity (61.17 pts) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of patients with venous leg ulcers who are more likely to experience persistent pain during treatment might be vital for the therapeutic outcomes. Previous studies confirmed unequivocally that ulcer pain jeopardizes significantly the activities of daily living and social contacts of the patients [ 3 , 8 , 16 , 19 , 23 , 33 , 36 , 37 , 38 , 39 ], deteriorates the quality of their life [ 3 , 22 , 30 , 33 , 35 , 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] and can even be a determinant of worse treatment compliance [ 49 ]. Therefore, the patients with unfavorable baseline profiles of risk factors, more prone to experience persistent pain, could be offered a complex therapeutic program, including also psychological intervention and consultations of a pain management specialist [ 50 ].…”
Section: Discussionmentioning
confidence: 94%
“…Physically, people with CVLUs experience symptoms such as odor, drainage, and leg swelling, which affect functional ability and physical appearance [ 8 ]. Self-management of CVLUs has been linked to , fatigue and pain [ 9 ], and physical exhaustion [ 10 ] from the intense care required. Psychological symptoms reported by people with CVLUs include fear that the ulcer will never heal, will get infected, or that an amputation may occur [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%